2019
DOI: 10.1167/tvst.8.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Volume Changes in Patients With Acute Eye Pain: A Voxel-Based Morphometry Study

Abstract: PurposeThe present study was attempted to compare the differences in gray matter volume (GMV) between the acute eye pain (EP) patients and the healthy controls (HCs) using voxel-based morphometry (VBM), and to explore the relationship with clinical features and behavioral performance.MethodsA total of 24 patients (17 males, 7 females) with acute EP and 24 (17 males, 7 females) age-, sex-, and education-matched HCs were recruited from the Ophthalmology Department of the First Affiliated Hospital of Nanchang Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…31 Accumulated neuroimaging evidence has indicated that the anterior cingulate cortex was involved in emotional regulation, cognitive processes, and specific motor functions. 11,37,38 Previously, Silkiss et al found thinning of the grey matter sheet in the right anterior cingulate and they linked it to the emotional disturbances in TAO. 11 Similarly, we also found decreased nodal properties in the right anterior cingulate, and negative correlations were observed between nodal degree in the right ACG and HARS as well as HDRS scores.…”
Section: Discussionmentioning
confidence: 99%
“…31 Accumulated neuroimaging evidence has indicated that the anterior cingulate cortex was involved in emotional regulation, cognitive processes, and specific motor functions. 11,37,38 Previously, Silkiss et al found thinning of the grey matter sheet in the right anterior cingulate and they linked it to the emotional disturbances in TAO. 11 Similarly, we also found decreased nodal properties in the right anterior cingulate, and negative correlations were observed between nodal degree in the right ACG and HARS as well as HDRS scores.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is possible that the image using IR may show a large difference between an inappropriate phantom and in‐vivo CSF. Studies utilizing tissue volumes are actively conducted with voxel‐based morphometry of brain tissue . In order to enhance the contrast between white matter and gray matter, the IR pulse may be used in advance.…”
Section: Discussionmentioning
confidence: 99%
“…We preprocessed the structural image data using the voxel-based morphometry toolbox (VBM8, http://dbm.neuro.uni-jena.de/vbm8/ ), Statistical Parametric Mapping (SPM8, http://www.fil.ion.ucl.ac.uk ), and MATLAB 7.9.0 software (R2009b; The Mathworks, Inc, Natick, MA, USA). The brains were divided into three parts as gray matter, white matter and cerebrospinal fluid using the default estimation options on VBM8, as previously described 18 . The preprocessed data were then standardized to conform to the Montreal Neurological Institute (MNI) criteria.…”
Section: Methodsmentioning
confidence: 99%